Evaluación de DDE en pacientes atendidos en la clínica de niños en la facultad de odontología de la UAN, sede Armenia, del año 2017 al 2021 (2023)
Alterations in dental enamel can be localized or generalized, qualitative or quantitative, their etiology is related to previous traumatic lesions, infections, irradiation, genetic disorders infections, irradiation, genetic disorders, exposure to excess fluoride, dioxins, perinatal health exposure to excess fluoride, dioxins, perinatal and postnatal health problems, maternal malnutrition, infectious maternal malnutrition, infectious diseases, among others. Among the types of enamel development developmental enamel defects include hypoplasia, which is a quantitative defect characterized by an enamel characterized by a thin enamel and hypomineralization, which is a qualitative defect mineral density, opacity, tooth sensitivity and tendency to fracture. sensitivity and tendency to fracture.